Clinical characteristics of children with epilepsy managed at an urban hospital in Africa: a retrospective study - Samia, P; Barr, A; Levi, SB; Donald, KA; Wilmshurst, JM; Newton, CR (International Child Neurology Association (ICNA), 2019)
Background Most children with epilepsy reside in resource-limited regions such as sub-Saharan Africa, where the majority of studies have been conducted in rural areas with limited investigations. Medical records from children with epilepsy seen at an urban hospital in Kenya were examined to provide a comprehensive description of epilepsy in children from this hospital.